2010
DOI: 10.1111/j.1468-0327.2009.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of employment protection legislation and financial market imperfections on investment: evidence from a firm-level panel of EU countries

Abstract: " Exploiting information from a panel of European firms we study the joint effect of EPL and financial market imperfections on investment, capital-labour substitution, labour productivity and job reallocation. We find that EPL reduces investment per worker, capital per worker and value added per worker in high reallocation sectors relative to low reallocation sectors, while increasing the average frequency at which firms adjust their capital stock. The reduction in capital per worker and value added per worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 66 publications
7
89
2
2
Order By: Relevance
“…The negative impact of employment protection on turnover was confirmed also by cross-country studies performed on aggregate data (see Gomez-Salvador et al, 2004;Messina and Vallanti, 2007;Boeri and Garibaldi, 2009). To similar conclusions arrive also studies exploiting difference-in-differences approach on OECD countries (see Micco and Pages, 2006;Haltiwanger et al, 2010;Bassanini et al, 2010;Cingano et al, 2010;and OECD, 2010), by which the negative relationship between dismissal costs and job flows is greater in industries with greater propensity to reallocate labor.…”
Section: Brief Review Of the Efficiency Effects Of Severance Paysupporting
confidence: 53%
“…The negative impact of employment protection on turnover was confirmed also by cross-country studies performed on aggregate data (see Gomez-Salvador et al, 2004;Messina and Vallanti, 2007;Boeri and Garibaldi, 2009). To similar conclusions arrive also studies exploiting difference-in-differences approach on OECD countries (see Micco and Pages, 2006;Haltiwanger et al, 2010;Bassanini et al, 2010;Cingano et al, 2010;and OECD, 2010), by which the negative relationship between dismissal costs and job flows is greater in industries with greater propensity to reallocate labor.…”
Section: Brief Review Of the Efficiency Effects Of Severance Paysupporting
confidence: 53%
“…Stricter employment regulations, namely, may decrease fi rms' business expectations, which may reduce their willingness to employ (Stubelj, 2010). Recent analyses of gross worker and job fl ows performed with the use of differencein-differences estimators on a cross-section of industry-level data showed that strict dismissal regulations reduce job turnover or gross worker fl ows, by which the negative relationship is stronger in industries where the need for labour reallocation is higher (see Micco and Pages, 2006;Bassanini et al, 2010;Haltiwanger et al, 2010;Cingano et al, 2010). Reduced job and worker fl ows result in worse job opportunities for workers, whereas their association with employment levels is ambiguous (for overview of studies see OECD, 2010).…”
Section: Employment Protection Legislationmentioning
confidence: 99%
“…3 In order to investigate this issue, we build and exploit a unique dataset including cross-country comparable hiring and separation rates 1 Search and matching models, such as those of Garibaldi (1998) or Mortensen and Pissarides (1999), also come to the conclusion that job mobility is negatively affected by the stringency of dismissal regulations. 2 See among others Autor et al (2007), Boeri and Jimeno (2005), Marinescu (2009), Gomez-Salvador et al (2004), Messina and Vallanti (2007), Haltiwanger et al (2008), Cingano et al (2010), and, for less conclusive findings, Bauer et al (2007), Martins (2009) andvon Below andThoursie (2010). 3 Obviously, workers might experience short spells of unemployment between the two dates.…”
Section: Introductionmentioning
confidence: 99%